PENGGUNAAN MEDIA PERMAINAN ULAR TANGGA UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS XI SMA AS-SHOFA PEKANBARU - Sahri Rahmadani Sahri Rahmadani; Rasmiwetti '; Johni Azmi Johni Azmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Research on the use of media game snakes and ladders have been done to find out how it affect the student achievement on the topic of Hydrocarbon in class XI IPA SMA As-Shofa Pekanbaru. This kind of research is experiment research with randomized control group pretest-posttest design. The sample consisted of two classes, namely class XI IPA-3 as the experimental class and class XI IPA-2 as a controls class, it randomly selected after normality test and homogeneity test. Experimental class is a class that was treated by learning using media game of snakes and ladders, while the control class is a class that is not treated using media game of snakes and ladders. Data analysis technique is the t-test. Based on the final calculation result obtained tvalue is 2.70 is greater than ttable is 1.67 with an increase in the use of media influence a game of snakes and ladders to student achievement is 16.84%, so it can be concluded that the use of the media game of snakes and ladders can improve the student’s achievement on the subject of hydrocarbons in class XI Science high School-As Shofa Pekanbaru.Keyword : Learning, snakes and ladders game, Learning Achievement, Hydrocarbon